2011
DOI: 10.1136/bmjopen-2011-000071
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse reflectance spectroscopy: diagnostic accuracy of a non-invasive screening technique for early detection of malignant changes in the oral cavity

Abstract: BackgroundStrong proof-of-principle for utilisation of diffuse reflectance spectroscopy, a non-invasive tool for early detection of malignant changes, has emerged recently. The potential of this technique in distinguishing normal tissue from hyperplastic and dysplastic tissues was explored.MethodsDiffuse reflectance (DR) spectra in the 400–700 nm region were obtained from the buccal mucosa of 96 patients and 34 healthy volunteers. The DR spectral data were compared against the gold standard biopsy and histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…Techniques such as reflectance spectroscopy 15 , fluorescence spectroscopy 16 and autofluorescence 17 are being used to extract information from oral mucosa on the basis of the interaction of light with endogenous tissue fluorophores. However, in vivo confocal microscopy reveals the actual cellular structures and as such is a form of in vivo histology.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques such as reflectance spectroscopy 15 , fluorescence spectroscopy 16 and autofluorescence 17 are being used to extract information from oral mucosa on the basis of the interaction of light with endogenous tissue fluorophores. However, in vivo confocal microscopy reveals the actual cellular structures and as such is a form of in vivo histology.…”
Section: Discussionmentioning
confidence: 99%
“…PCA and LDA were performed over the fluorescence and reflectance spectral data [16,17]. PCA was used to identify the orthogonal components of the spectra with maximum variance within the complete data set.…”
Section: Discussionmentioning
confidence: 99%
“…A current DRS system typically consists of an imaging device for recording diffuse reflectance images and a fiber-optic probe for relaying light to and from the instrument . Some studies have showed that information about tissue transformation, obtained in vivo with the aid of the oxygenated hemoglobin spectral ratio (R545/R575) algorithm, was able to differentiate normal mucosa, hyperplasia, dysplasia, and OSCC with high sensitivity and specificity (Table 1) (Mallia et al 2008(Mallia et al , 2010Jayanthi et al 2011). Moreover, Stephen et al (2013) suggested that DRS could be very effective as a screening tool for the location of oral PMDs.…”
Section: Diffuse Reflectance Spectroscopymentioning
confidence: 99%
“…The diffusely reflected emanating light is greatly affected by tissue morphology, such as nuclear size, distribution, epithelial thickness, collagen content, and the amount of oxy-and deoxy-hemoglobin in the exposed tissue, all of which can vary during carcinogenesis of epithelial tissue (Schwarz et al 2008;Jayanthi et al 2011). A current DRS system typically consists of an imaging device for recording diffuse reflectance images and a fiber-optic probe for relaying light to and from the instrument .…”
Section: Diffuse Reflectance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation